The Promising Role of miR-21 as a Cancer Biomarker and Its Importance in RNA-Based Therapeutics - Diana Bautista-Sánchez; Cristian Arriaga-Canon; Abraham Pedroza-Torres; Inti Alberto De La Rosa-Velázquez; Rodrigo González-Barrios; Laura Contreras-Espinosa; Rogelio Montiel-Manríquez; Clementina Castro-Hernández; Verónica Fragoso-Ontiveros; Rosa María Álvarez-Gómez; Luis A. Herrera (Elsevier, 2020)
MicroRNAs are small noncoding transcripts that posttranscriptionally regulate gene expression via base-pairing complementarity. Their role in cancer can be related to tumor suppression or oncogenic function. Moreover, they have been linked to processes recognized as hallmarks of cancer, such as apoptosis, invasion, metastasis, and proliferation. Particularly, one of the first oncomiRs found upregulated in a variety of cancers, such as gliomas, breast cancer, and colorectal cancer, was microRNA-21 (miR-21). Some of its target genes associated with cancer are PTEN (phosphatase and tensin homolog), PDCD4 (programmed cell death protein 4), RECK (reversion-inducing cysteine-rich protein with Kazal motifs), and STAT3 (signal transducer activator of transcription 3). As a result, miR-21 has been proposed as a plausible diagnostic and prognostic biomarker, as well as a therapeutic target for several types of cancer. Currently, research and clinical trials to inhibit miR-21 through anti-miR-21 oligonucleotides and ADM-21 are being conducted. As all of the evidence suggests, miR-21 is involved in carcinogenic processes; therefore, inhibiting it could have effects on more than one type of cancer. However, whether miR-21 can be used as a tissue-specific biomarker should be analyzed with caution. Consequently, the purpose of this review is to outline the available information and recent advances regarding miR-21 as a potential biomarker in the clinical setting and as a therapeutic target in cancer to highlight its importance in the era of precision medicine.